Circulating cytokines as determinants of weight loss-induced improvements in insulin sensitivity - Weiss, Edward P. (Endocrine, 2016)
PURPOSE: Dietary calorie restriction (CR) and exercise (EX) promote weight loss and may have additive effects for improving insulin sensitivity, independent of weight loss. It is not known if these effects are attributable to changes in circulating cytokines. We evaluated the hypothesis that modest, matched weight loss induced by CR and EX have additive effects on circulating cytokines and these changes correlate with improvements in insulin sensitivity. METHODS: Overweight and sedentary women and men (n=52, 45–65y) were randomized to undergo 7% weight loss by using 3–6 months of CR, EX, or a combination of both (CREX). Concentrations of cytokines and hormones were measured in fasting and oral glucose tolerance test (OGTT) blood samples. Insulin sensitivity was estimated based on OGTT glucose and insulin. RESULTS: With all groups combined fasting leptin (p<0.0001) and HMW adiponectin (p=0.04) decreased and pentraxin-3 increased (p<0.0001), in a manner that correlated with improvements in insulin sensitivity (all p≤0.0002). These changes, combined with decreases in glucose-dependent insulinotropic polypeptide from the OGTT, explained 63% of the variance (p<0.0001) in insulin sensitivity improvements. EX and CR had additive effects on leptin, with a similar trend for HMW adiponectin. MCP-1 and CRP concentrations did not change. CR and EX had opposite effects on soluble TNF receptor-1. CONCLUSIONS: Modest weight loss in overweight adults decreases serum leptin and HMW adiponectin, and increases pentraxin-3 concentrations in a manner that correlates with increased insulin sensitivity. Exercise has additive effects to those induced by CR for reductions in leptin and possibly adiponectin. These changes may contribute to the additive effects of CR and exercise for improving insulin sensitivity.